#TITLE_ALTERNATIVE# - Aldiamar (NIM 250 04 061), Fahmi
Abstract: Seismic hazard analysis and design spectral response for Suramadu bridge was done to accommodate the lack of Indonesia seismic hazard map that fulfill the requisite design criteria on Bridge Management System and International Building Code 2006, which is 4950 return period that accommodate 100 years bridge design life and 2 percent probability of exceedance. Seismic hazard analysis software named EZFRISK that used in this researh was using a total probability theorm and the 3D earthquake source model which based on the seismotectonic and regional fault identification using the reginal geology map. Seismic source area which contribute the site location assumed to have a radius of 500 km from the Suramadu bridge location. 1 dimensional wave propagation from bedrock to the surface was done using NERA software which required soil stratification and shear wave velocity parameter as input parameter. Seismic hazard analysis using the same return of period show that maximum acceleration on bedrock and at the surface according to SNI-1726-2002 for Surabaya region was lower than the analysis using the 3D earthquake source model. Therefore a detailed evaluation and examination to the Indonesia hazard map on SNI-1726-2002 must be done. A standard seismicity parameter and guideline to make Indonesia seismic hazard map was needed to avoid the publicity of different variation of Indonesia seismic hazard map in the future.